Effects of chicken manure and pig manure (organic fertilizers) applied at different frequencies on milkfish production - Odunwa, Hyancinth Iffanyi (Iloilo University of the Philippines in the Visayas, 1986)
An experiment comparing the effects of different frequencies of application of the same amount of chicken manure and pig manure on brackish water pond productivity, milkfish yield and physic-chemical parameters of pod water and soil was conducted at the Brackishwater Aquaculture Center, UPV College of Fisheries, Leganes, Iloilo, Philippines. The treatments were: 1 and 2, chicken and pig manure respectively, applied at 100 kg/ha five times a week; 3 and 4, chicken and pig manures respectively, applied at 250 kg/ha two times a week; and 5 and 6, chicken and pig manures respectively, applied at 500 kg/ha once a week. The treatments were on moisture free or dry weight basis. All physic-chemical parameters monitored showed a general decrease in pH, increase in % organic matter, available phosphorus and total nitrogen for pond soil after the experiment while the water parameters fluctuated widely. Temperature and salinity plunged from 36.50C and 40 ppt during the summer months to as low as 19.90C and 15 ppt respectively with the on-set of the rainy season. Significant differences were observed in pond water pH, temperature (before sunrise and sunset), dissolved oxygen (before sunrise and sunset) and primary productivity which also showed consistent higher values in treatments with chicken manure than those with pig manure. The pond water color was affected by the heavy manure loading but never showed trends of becoming soup-like in consistency. The highest mean net fish yield of 547.63 kg/ha was obtained in treatment 5 while treatment 2 gave the lowest mean net fish yield of 454.63 kg/ha. Fish condition factor ranged from as high as 1.02572 to as low as 0.99715. Generally, these are lower than most published values for milkfish. The percentage fish survival was considerably satisfactory ranging from 85% to 98.3%. Comparatively, the use of chicken manure resulted in higher yields than pig manure, and in terms of application frequency, the once a week treatment for both manures were better than the two times and five times a week treatments.
Thesis (M.S. Fisheries-Aquaculture) -- Iloilo : University of the Philippines in the Visayas, January 1986.
Keywords: Chicken manure (organic fertilizer); Pig manure (organic fertilizer)